Local community participation in ecotourism at National Park in Pahang, Malaysia - Tan, Sok Hu; Lim, Evelyn Ai Lin; Mamat, Mohd Parid (Forestry Department Peninsular Malaysia, 2020)
Ecotourism has become one of the fastest-growing sectors in the world's tourism industry. The participation of local communities living near protected areas is essential to the development of the ecotourism sector. However, there is still a lack of information on local communities' participation in ecotourism development at the National Parks in Malaysia. The present study determines local communities' level of participation in ecotourism development at the three National Parks, specifically Taman Negara Kuala Tahan (TNKT), Taman Negara Kuala Koh (TNKK) and Taman Negara Merapoh (TNM). It also identifies the socioeconomic factors that influence local communities' level of participation. The study involved 400 respondents, and information on their level of participation was collected using a face-to-face interview that is guided by a questionnaire. Results show a very low or low level of participation among the local communities at the different stages in TNKT, TNKK, and TNM. However, local communities are more involved in the benefits-sharing stage activities. The socioeconomic factors did not affect the level of local communities' participation at TNKK. Age was a significant factor in the benefits-sharing stage for TNKT and TNM. At the same time, household income is the only factor that significantly influences local communities' participation in the planning, implementation, monitoring, and benefits-sharing stages at TNKT and TNM. The findings of the study serve as an important guide to the stakeholders in developing a more community participative ecotourism initiative to achieve sustainable tourism in National Park.